Distinct phenotypes of salivaricin-producing Ligilactobacillus salivarius isolated from the gastrointestinal tract of broiler chickens and laying hens - A.G. Elnar; Y.J. Jang; B.G. Eum; M.H. Kang; G.W. Hwang; D.Y. Kil; G.B. Kim (Poultry Science, 2025)
Ligilactobacillus salivarius harbors bacteriocin genes in its repA-type megaplasmid, specifically salivaricin P (salP), a class IIb bacteriocin. This study aimed to differentiate 25 salP-positive Lig. salivarius strains isolated from the gastrointestinal tract (GIT) of broilers and laying hens. Results showed that 12 isolates were classified as Type A, with active bacteriocins, while the rest were Type B, with no active bacteriocins. In vitro and in silico characterization of salP bacteriocins revealed narrow-spectrum antibacterial activity against Listeria monocytogenes and Enterococcus faecalis. SalP bacteriocins were predicted as positively charged, hydrophobic, small molecular weight (α, 4.097 kDa; ß, 4.285 kDa) bacteriocins with characteristic GXXXG motif. Investigation of the salP gene cluster based on genomic data revealed that Type B strains lacked the lanT and hlyD genes that encode export proteins dedicated to the modification and extracellular transport of mature salP peptides. However, two Type B strains (B4311 and B5258) showed inhibitory activity against L. monocytogenes ATCC19114. Multiplex PCR analysis and synteny mapping analysis revealed that B4311 and B5258 strains harbored the lanT gene, highlighting the importance of LanT protein in the cleavage of leader peptide and excretion of mature peptides. Further analysis revealed that the resistance of Type B strains to salP was attributable to the presence of a dedicated immunity protein, blurring the evolutionary significance of producing active bacteriocins for competitive advantage. Additionally, the loss of export proteins occurred in a polyphyletic manner, consistent with the genetic plasticity of the repA-type megaplasmid. This suggests that the loss of lanT and hlyD is likely in the presence of limited nutritional competitors. In conclusion, the observed differences in salivaricin production of Lig. salivarius exist independent of isolation host and that Type A and Type B strains can coexist in the same environment. Finally, the functional characterization of active salP allows for a better understanding of its potential to control specific bacteria in human food and animal production.